Testing for language teachers - Hughes, Arthur (Cambridge University Press, 2003)
This second edition remains the most practical guide for teachers who want to have a better understanding of the role of testing in language teaching. It has a new chapter on testing young learners and expanded chapters on common test techniques and testing overall ability